Gastrointestinal Polyps in Children - Li-Chun Wang; Hung-Chang Lee; Chun-Yan Yeung; Wai-Tao Chan; Chuen-Bin Jiang (Pediatrics and Neonatology)
Gastrointestinal polyps are common in children. The purpose of this study was to review the clinical manifestations, diagnostic procedures, endoscopic findings, management, pathology, and recurrence of gastrointestinal polyps in children at Mackay Memorial Hospital. Methods: We retrospectively reviewed the charts of 50 children with a diagnosis of gastrointestinal polyps managed at Mackay Memorial Hospital between January 1984 and April 2007. Demographic data; clinical features; polyp size, number and location; endoscopic findings; management; pathology; and information on recurrences were extracted from the clinical records. Results: The distribution of polyps in the 50 patients included gastric (4 patients), duodenal (2), ileocecal (4) and colorectal polyps (40). All patients with gastric polyps presented with vomiting, and three of the four patients with ileocecal polyps presented with intussusception. The mean age of the 40 patients with colorectal polyps was 6.8 years. The majority of those polyps were in the rectosigmoid colon; 36 patients presented with hematochezia. Solitary polyps were identified in 33 patients and multiple polyps were identified in seven patients. Most of the colorectal polyps were less than 2 cm in diameter. Histologically, the most frequent type was juvenile polyp. Conclusion: Gastrointestinal polyps in children are usually benign. Pediatricians treating a child with a gastrointestinal polyp should pay attention to the immediate complications of the polyps, such as intussusception or bleeding, the extraintestinal manifestations and long-term risk for malignancy.